Seven keys to unlock autism : - Hall, Elaine (Jossey-Bass, 2012)
This groundbreaking book outlines seven integrated keys for educators and parents to make meaningful connections with children on the autism spectrum.Seven Keys reveals the seven-step program that has proven so successful for children in the Miracle Project After reading Seven Keys teachers and parents will better understand this puzzling disorder and be able to help children with autism draw connections and form more meaningful relationships.Seven Keys to Unlock Autism offers readers strategies for creating a personal skill set to make their encounters with autistic children as successful and rewarding as possible